Pembelajaran penjasorkes Pada Masa Pandemi Covid-19 Di SMA Negeri 1 Pecangaan Kabupaten Jepara Tahun 2021 (Universitas Negeri Semarang, 2022)
This study aims to describe and review the planning, implementation, evaluation of learning of fishermen during the covid-19 pandemic. The methods used in this study are qualitative with a descriptive approach. Data is obtained through interviews, observations. and documentation conducted at SMA Negeri 1 Pecangaan Jepara Regency, then analyzed through data reduction, descriptive presentation of data and drawing conclusions. The results of this study are known that in SMA Negeri 1 Pecangaan in learning planning during the covid-19 pandemic still uses syllabus and rpp offline, but prepares teaching materials, media, sources, learning methods, and assessments that have been adjusted to the conditions of the covid-19 pandemic. The implementation of learning is carried out online in the form of asynchronous through google classroom, whatsapp, LMS according to the PJJ schedule. Evaluation of learning during the covid-19 pandemic only evaluates learning outcomes using two aspects only, namely affective and cognitive. Assessment of the affective aspect is obtained by looking at the discipline of students in accessing learning and collecting assignments. Assessment of the cognitive aspect is usually done by giving assignments at the end of learning and PTS / PAS.